Wound in the oral cavity by a projectile from a firearm with unusual exit course - Arroyo-Anglas, Hugo (2011)
We report an adult male who was admitted to hospital for emergency after being shot by a firearm, presenting a bullet entry hole in the upper lip of the mouth, finding no outlet, radiological examination shows shrapnel oral cavity and the presence of a foreign body in the digestive tract, which migrates to the rectum to be expelled for five days, being compatible with the projectile, after clinical response to medical management.